Changes in Motivation, Socialization, Wellness and Mental Health in Youth Long-Distance Runners During COVID-19 Social Distancing Restrictions - Bazett-Jones, David M.; Garcia, Micah C.; Taylor-Haas, Jeffery A.; Long, Jason T.; Rauh, Mitchell J.; Paterno, Mark V.; Ford, Kevin R. (Frontiers in Sports and Active Living, 2021)
Purpose: The COVID-19 pandemic impacted the sporting and exercise activities of millions of youth. Running is an activity that could be maintained while social distancing restrictions were implemented during the pandemic. However, a recent study has indicated that youth runners reported lower running distance, frequency, and intensity during COVID-19. The reason for this reduction and the impact on overall well-being is unknown. Therefore, the purpose of this study was to determine if the social distancing restrictions during the 2020 COVID-19 pandemic influenced running motives, socialization, wellness and mental health in youth long-distance runners. Methods: A customized, open online questionnaire was provided to runners 9 to 19 years of age who participated in long-distance running activities including team/club cross-country, track and field (distances ≥800 m), road races, or recreational running. Participants responded to questions about demographics, motive for running, and wellness (sleep quality, anxiety, running enjoyment, food consumption quality) six-months before as well as during social distancing restrictions due to COVID-19. Wilcoxon signed rank tests compared differences for ratio data and Chi-square tests were used to compare proportions before and during COVID-19 social distancing restrictions. Statistical significance was set at p≤.05. Results: A total of 287 youth long-distance runners (male=124, female=162, unspecified=1; age=15.3±1.7 years; running experience=5.0±2.3 years) participated. Compared to their pre-COVID-19 responses, youth long-distance runners reported lower overall motivation to run (p<.001) and changes to most motive rankings (p<.001 to p=.71). The proportion of youth running alone increased during COVID-19 (65.8%) compared to pre-COVID-19 (13.8%, p<.001). Youth long-distance runners also reported less running enjoyment (p=.001), longer sleep duration (p<.001), lower sleep quality (p=.05), more anxiety (p=.043), and lower food quality consumed (p<.001) during COVID-19 social distance restrictions. Conclusion: The COVID-19 social distancing restrictions resulted in significant decreases in motivation and enjoyment of running. The removal of competition and team-based interactions likely had a role in these decreases for this population. Continuing team-based activities (e.g. virtual) during social distancing may help with maintaining motivation of youth long-distance runners. Reduced running occurred concurrently with reduced overall wellbeing of youth long-distance runners during the COVID-19 pandemic.